HUBUNGAN ANTROPOMETRI DENGAN KURSI KERJA DI KANTOR PELAYANAN PERBENDAHARAAN NEGARA MOJOKERTO - Vrilly Andhini (Universitas Airlangga, 2018)
Chairs are an important component in determining comfort while sitting or doing a job with sitting. The aim of the research is to analyze the suitability between the size of the table and chair with anthropometry of the employee’s body. The number of respondents is 20 people. The variables of the study are measure of anthropometry and workstation. This is a descriptive research and using cross sectional approach. The measured variables are body anthropometry such as popliteal height, politeal but, hip width, shoulder height, shoulder width, elbow height. Variable work seats include seat height, seat base, length of seat base, width of seat, high backrest, width of backrest, elbow height. The results show that the dimensions of the workstation that corresponds to the body dimensions of the width of the seat base with the width of the hip the height of the backrest with the height of the sitting shoulder and the length of the elbow rest with the length of the forearm Dimensions that are inconsistent with the anthropometry of the body with the height of the chair with the popliteal height the length of the sitting base with popliteal buttock the width of the backrest with shoulder width the height of the elbow rest with the height of the sitting elbow. Conclusion is work chair is not accordance with anthropometry of employees because only 3 dimensions of work chairs are compatible with employee anthropometry.Keywords: anthropometry, chair, dimensions